퍼지 알고리즘을 이용한 유중 변압기의 안전진단 및 평가에 관한 연구 - 金榮日(Young-il Kim) (전기학회 논문지 P권, 55(4), 2006)
In this paper, safety algorithm of transformer is introduced for the sake of MV/LV distribution customers by using fuzzy theory. The current-carrying capacity of transformer is usually determined by the maximum temperature at which the transformer is permitted to operate. Overload of transformer has an effect on transformer utilization rate and maximum temperature rises as well as maximum ambient temperature of insulating materials. Therefore, we proposed the safety algorithm considering the overload of transformer and ambient temperature in this paper. We introduced the correlational equations between each parameters using experimental data of IEEE std C57.91-1995, and deduced the result using fuzzy reasoning. We guessed the safety algorithm making a diagnosis for the safety status of oil-immersed transformer.